Establishment and application of a SNP molecular identification system in Grifola frondosa - Diao, Bin; Xu, Zhixiang; Liu, Min; Zhang, Guoli; Wang, Guangyuan; Zhang, Yinghao; Tian, Xuemei (Frontiers in Microbiology, 2024)
Germplasm resources of edible mushrooms are essential for the breeding of varieties with improved traits. Analysis of the genetic diversity of Grifola frondosa germplasm resources and clarification of the genetic relationships among strains can provide valuable information for the selection of breeding parents. A total of 829,488 high-quality SNP loci were screened from 2,125,382 SNPs obtained by sequencing 60 G. frondose. Phylogenetic analysis, PCA, and population structure analysis based on the high-quality SNPs showed that the 60 strains could be divided into five subgroups, and the clustering results were consistent with the geographical distributions of these strains. Based on high-quality SNP loci, a core collection containing 18 representative germplasm resources was constructed, and 1,473 Kompetitive Allele-Specific PCR markers were obtained. A total of 722 SNP markers in the exonic regions were screened using KASP-genotyping experiments, and 50 candidate SNP markers and 12 core SNP markers were obtained. Genetic fingerprints of G. frondosa germplasm resources were constructed based on the selected SNP markers; these fingerprints provide an accurate, rapid, convenient, and efficient method for the identification of G. frondosa germplasm resources. The results of this study have important implications for the preservation and utilization of G. frondosa germplasm resources and the identification of varieties.